2008
DOI: 10.1167/iovs.07-1342
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Ocular Rigidity Based on Measurement of Pulse Amplitude Using Pneumotonometry and Fundus Pulse Using Laser Interferometry in Glaucoma

Abstract: The present study indicates increased ocular rigidity in patients with POAG. This is compatible with a number of previous animal experiments and supports the concepts that the biomechanical properties of ocular tissues play a role in the diseases process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 39 publications
5
100
0
Order By: Relevance
“…18,42 A growing body of research has shown that the sclera becomes stiffer in glaucoma. 7,43,44 These latter findings would support a link between myofibroblast-mediated detrimental sclera remodeling and mechanical damage to the ONH.…”
Section: Discussionmentioning
confidence: 73%
“…18,42 A growing body of research has shown that the sclera becomes stiffer in glaucoma. 7,43,44 These latter findings would support a link between myofibroblast-mediated detrimental sclera remodeling and mechanical damage to the ONH.…”
Section: Discussionmentioning
confidence: 73%
“…Assuming that FPA is proportional to the choroidal volume change during the cardiac cycle, PV (as assessed with pneumotonometry) and choroidal volume change (as calculated from FPA) should be equal. However, the ratio of choroidal volume change to PV may depend on two additional factors: ocular volume and ocular rigidity (Hommer et al 2008).…”
Section: Pcimentioning
confidence: 99%
“…25 Functional MRI, however, has a temporal resolution on the order of 10 seconds. Precision pneumotonometry, 26 combined with detection of fundus pulsation amplitude using laser interferometry, 27 provides a means for estimating overall ocular stiffness, but cannot distinguish the contribution of any particular layer or position. While a recent study described use of ultrasound to investigate the elastic properties of the retina and choroid by measurement of thickness changes of these layers with compression of the eye, 28 this approach differs fundamentally from the technique described here, since ARFI detects the dynamic effects of transient compression rather than the effects induced by static loading.…”
Section: Discussionmentioning
confidence: 99%